The Politics of Juan Ramón Jiménez as Politics of the Natural Landscape of the People - Gutiérrez-Pozo, Antonio (2025)
This article analyzes the ethic and politic of Juan Ramón Jiménez. His ethical and political program does not exist apart from his poetic attitude. His poetry is not simply a means of transmitting a particular political ideology. Juan Ramón considers that every poet, as a poet, already carries with him an ethic and a politic. Authentic poetry is itself inevitably ethical and political. The fundamental concepts that develop Juan Ramón’s ethic and politic are vocation and aristocracy of outdoors. The essential goal Juan Ramón sets forth is the realization of vocation or personal self, that is, the perfect self of each one of us. Each of us is destined to realize the latent self that we carry with us. In order to fulfill this personal vocation we must freely and pleasantly give ourselves to the activity of self-realization. This is what Juan Ramón calls pleasantly work, a work that arises freely from the individual, without impositions. The political goal would be a society that makes possible the people’s self-realization through work. The final and main thesis consists in affirming that in order to be ourselves we need our natural landscape and our people, because the human being is a being with roots.